PROBLEMATIKA YANG TIMBUL DALAM PERJANJIAN JUAL BELI PAKET WISATA OLEH BIRO PERJALANAN - Surya Budi (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTPublic travel agency as the organizer of the tour package services has a very important role, because the public travel agency is a company that has a direct relationship with tourists and who is responsible for the implementation of tour packages services as well as he (Public Travel Bureau) has a duty And function as a service provider party that aims to provide the best service possible to tourists, so from here is expected to grow a sense of confidence from tourists to the public travel agency that obtain the best service during the tour or tour to where they want the Certainly has been listed in the tour package. Therefore, public travel agents should always improve the quality of service to always get the trust of the tourists. However, in practice not all public travel agencies undertake such an action or effort, sometimes there are some who feel that after gaining the trust of the tourists then abusing the trust in various ways aimed solely for the benefit - many without paying attention to the risks to be faced. The number of cases of buying and selling in the world of tourism in particular, we can know about the deficiencies that are essential when viewed from the juridical side. Which in principle can be divided into two namely: Because from within, this includes the relationship within the Travel Bure itself. Outside, it covers causes such as travel disruption, payment deductions, tourist security alone, Overmacht,